LITERATURE REVIEW RELATIONSHIP OF WORK DISCIPLINE, REWARD AND JOB TRAINING ON WORK ACHIEVEMENT - Hermawan, Eric (Dinasti Publisher, 2022)
The Literature Review article on the Relationship of Work Discipline, Reward and Job Training to Job Performance is a scientific article that aims to build a research hypothesis on the influence between variables that will be used in further research, within the scope of Human Resource Management. The method of writing this Literature Review article is using the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this study are: 1) Work Discipline is related to Work Performance; 2) Rewards are related to Work Performance; and 3) Job Training related to Job Performance. Apart from these 3 exogenous variables that affect the endogenous variable of Work Achievement, there are still many other factors including the variables of Motivation, Skill and Education.